STUDENTS’ ERROR ANALYSIS IN SOLVING PROBABILITY STORY QUESTIONS BASED ON REVISED NEWMAN THEOREM - Sani, Dyah Nirmala; Rosnawati, R (Jurnal Pendidikan Matematika (JUPITEK), 2022)
Generally, students still need help working on story-shaped questions. This error is natural, but if it continues, it will harm the mastery of the next material. The ability to solve story questions is closely related to numeracy skills, therefore knowing the location of the difficulties using the revised Newman theorem and the causal factors will help students achieve higher learning outcomes. This research was a quantitative descriptive approach, with the research subjects of junior high school students as many as 152 students. The instruments used were diagnostic tests and questionnaires. Each had an estimated reliability of 0.701 and 0.705 with good qualifications. The results show that students' most frequent types of errors in solving story questions on empirical and theoretical probabilities were 43% transformation errors, 36% comprehension errors, 15% process skill errors and encoding errors by 6%. The specific factors of student errors are not thorough students, being in a hurry, having difficulty understanding the questions, did not master the material, forgetting the formula, hesitating in determining the formula, not re-check the answers, and were unable to write the final project answers/conclusions. Interest and motivation factors as well as society factors are the general factors that most influence the mistakes made by students